INTRA SPECIFIC VARIATION OF THE SPOTTED-WINGED FRUIT BAT Balionycteris maculata (THOMAS, 1893) (CHIROPTERA, PTEROPODIDAE) FROM SUMATERA, .INDONESIA - Ibnu Maryanto (Treubia, 2003)
The spotted winged bat (Balionycteris maculala) is recorded for the first time in Sumatra, Indonesia. The morphoiogy of 13 specimens from Sumatra was compared with that of specimens from Durian (Riau Archipelago) and Kalimantan-lndonesia. Univariate and multivariate analyses show that the Sumatran population is both significantly smaller in a number of characters and some differences in shape occur between Sumatran and Kalimantan specimens. The Sumatran population is similar in morphology to that of Durian Island. The Sumatran and Durian island specimens are referred to as Balionycteris maculata seimundi.